Molecularly Imprinted Silica Matrix In Detection Of Creatinine - Florence, Chan (Universiti Sains Malaysia, 2017)
Serum creatinine concentration is broadly interpreted as a measure of the glomerular filtration rate (GFR) and is used as an index of renal function in clinical practice. The traditional Jaffe’s reaction used to measure the serum creatinine concentration, is subjected to interferences and hence lose its specificity. In order to improve the analysis method, molecularly imprinted polymer (MIP) is studied due to its superb capability of recognizing targeted molecules selectively. Based on tetraethoxysilane (TEOS) as monomers and Al3+ as cross-linker, a molecularly imprinted silica matrix was synthesized via sol-gel method for the selective adsorption of creatinine. SEM results revealed that MIP exhibited more porous structure compared to the non-imprinted counterpart, while nitrogen adsorption-desorption analysis disclosed that the specific surface area of MIP (570.32 m2g-1) was larger than that of NIP (412.47 m2g-1). Rebinding test was performed at 30ᵒC for 24 h to assess the adsorption ability of both MIP and NIP. The MIP was found to have good imprinting factor (1.34 ± 0.26) over the NIP. The effects of temperature and solvent on the adsorption process were studied. The thermodynamic parameters of MIP and NIP were determined from the adsorption conducted at various temperatures (negative value of ΔGᵒ, positive values of ΔHᵒ and ΔSᵒ), indicated that binding system for MIP was spontaneous, endothermic, and entropy gained. The solvent effect was carried out with deionized water (highest polarity), methanol, ethanol and 2-propanol (lowest polarity) as solvent. The solvent-adsorbate interaction played important role in determining the amount of Cre adsorbed by the MIP. Solvent with higher polarity (water) forms more hydrogen bonds with Cre, leading to stronger interaction forces with it, thus, reduced the possibility for Cre to be adsorbed. Furthermore, selectivity tests were also been performed in this work to evaluate the discrimination ability of the MIP. The results demonstrated that MIP has higher affinity for the template, Cre over its analogues (Cr and 2-pyr) in single component adsorption. In binary solutions, selectivity of MIP for Cre over 2-pyr was high (3.30±0.34); however, the selectivity over Cr was low (0.46±0.12). In conclusion, Cre-based MIP was successfully synthesized, which is feasible to be used as a diagnostic tool for renal functionality.